1998
DOI: 10.1007/s007010050079
|View full text |Cite
|
Sign up to set email alerts
|

Mature Teratoma of the Lateral Ventricle: Report of Two Cases

Abstract: In this paper, two cases with mature teratoma of the lateral ventricle are presented. Teratomas are rare intracranial tumours and the most common location is in the midline pineal region. Lateral ventricle as the site of location is very rare. Between the years 1975 and 1996, 120 cases were operated on for lateral ventricle tumours at the University of Ankara, Department of Neurosurgery, and only two cases (% 1.6) were histologically identified as mature teratomas. It is generally accepted that benign teratoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…There have been cases reported of teratomas involving the ventricular system, Sylvian fissure, basal ganglia, pituitary fossa, cavernous sinus, middle ear space, petrous portion of the temporal bone, and middle cranial fossa. 6 7 8 9 10 11 12 13 To our knowledge, this is the first case report of an intracranial teratoma involving the temporal bone with extension into the cerebellopontine angle. Li et al 14 recently published their case of a 4-year-old girl who presented with fevers, headache, and purulent drainage from her ear.…”
Section: Discussionmentioning
confidence: 79%
“…There have been cases reported of teratomas involving the ventricular system, Sylvian fissure, basal ganglia, pituitary fossa, cavernous sinus, middle ear space, petrous portion of the temporal bone, and middle cranial fossa. 6 7 8 9 10 11 12 13 To our knowledge, this is the first case report of an intracranial teratoma involving the temporal bone with extension into the cerebellopontine angle. Li et al 14 recently published their case of a 4-year-old girl who presented with fevers, headache, and purulent drainage from her ear.…”
Section: Discussionmentioning
confidence: 79%
“…Sano [36] and Ogawa et al [37] revealed the combination of surgery and radiotherapy had good curative effect on mature teratoma with a 10-year overall survival rate of up to 93%. [36] However, Selcuki et al [38] and Jakacki [39] argued that mature teratoma was not sensitive to radiotherapy, but could only cause brain trauma. They believed that mature teratoma is a potentially resectable, surgically curable tumor.…”
Section: Review Articlementioning
confidence: 98%
“…Moreover, the development of mature teratoma in the third ventricle in postadolescent age is extremely unusual. Despite some controversies, total extirpation of the tumor is thought to be the gold standard for treatment of mature teratoma and generally leads no recurrence (7,8). We present a rare case of intraventricular germinoma occurring 30 months after a total resection of mature teratoma in the third ventricle.…”
Section: Introductionmentioning
confidence: 97%
“…* (1,6), and rarely in the cerebellar vermis (1) and lateral ventricles (8,14), whereas most germinomas arise in suprasellar cistern, the third ventricle, and less frequently, in the lateral ventricles (6, 13, 15). There have hitherto been only six cases of metachronous GCTs in which a germinoma occurred after total removal of a pineal (16)(17)(18)(19)(20) or intrasellar teratomas (21) in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation